1381. Impact of Total Body Weight on Efficacy of Ceftriaxone in Obese Patients. (26th November 2018) - Wagner, Jamie L; Loper, J Taylor; Morrison, Austin R; Stover, Kayla R; Barber, Katie E
Abstract: Background: Ceftriaxone (CRO), while highly protein bound, retains a small volume of distribution. Obese patients have larger volumes of distributions and higher clearance than nonobese patients. The effect of these differences on the pharmacokinetics and efficacy of CRO remain unclear. Methods: This retrospective cohort study included adult in-patients who received CRO for ≥72 hours as definitive monotherapy from July 2015 to July 2017. Patients were excluded if there was a lack of adequate source control at 72 hours or if there was a polymicrobial infection requiring multiple antibiotics. Obesity was defined as BMI ≥30 kg/m 2 . The primary outcome was clinical treatment failure, defined as changing therapy at >72 hours due to clinical worsening, leukocytosis (WBC > 10 × 10 9 /L), fever (single temperature >100.9°F) for >72 hours, or readmission to the hospital within 30 days for re-infection. Secondary outcomes included discharge disposition and 30-day readmission. Results: One hundred one patients were included: 39 obese patients and 62 nonobese patients. Median [IQR] age was 62 [51–70] years; 55% males. Median weight was 103 [95–120] kg in obese patients vs. 66 [58–77] kg in nonobese patients ( P < 0.001). There were no differences in comorbidities (Charlson 3[1–5] obese vs. 2[1–4] nonobese; P = 0.293). Infection sources were similar: urinary tract (54% obese vs. 52% nonobese; P = 0.827), respiratory (28% obese vs. 23% nonobese; P = 0.524), bloodstream (20% obese vs. 23% nonobese; P = 0.806). The most common causative organism was E. coli (48%). There were no differences in CRO regimen between groups (1g q24h: obese 54% vs. nonobese 69%; P = 0.115). Treatment failure occurred in 24 (61%) obese patients compared with 25(40%) nonobese patients ( P = 0.038). Obese patients had delayed resolution of leukocytosis (54% vs. 29%, P = 0.013). Eight patients died (13% obese vs. 5% nonobese; P = 0.255); 82% of patients were not readmitted within 30 days. Conclusion: Obese patients treated with ceftriaxone had higher rates of treatment failure compared with nonobese patients. While not statistically significant, there was numerically higher mortality in obese patients compared with nonobese patients. Obese patients may be slow to recover from infection when treated with CRO. Disclosures: All authors: No reported disclosures.